Evaluation of Fiscal and Non-Fiscal Policies for Electric Vehicles—A Multi-Criterion Sorting Approach - Clímaco, Isabel (2023)
This work presents a multi-criterion approach to evaluate the performance of countries regarding fiscal and non-fiscal policies for promoting electric vehicles. The ELECTRE TRI method is used to classify the performance of countries into categories according to the degree of fulfilment of those policies. This multi-criterion decision analysis method assigns the entities under evaluation to predefined ordered categories of merit (sorting problem). This is accomplished by comparing the entities under evaluation with reference profiles that establish the frontiers between the categories. The model considers fiscal (vehicle registration tax benefits, taxation of internal combustion engine company cars, consumer purchase incentives, tax shares in consumer prices of gasoline vs. electricity) and non-fiscal (traffic regulation incentives, charging infrastructure) potential policies to define a comprehensive set of evaluation criteria. The ELECTRE TRI method allows for robust conclusions by enabling the comparison of results obtained with different preference expression parameters, according to the distinct aims and scope of the decision problem. Illustrative results are presented allowing for the assessment of each country’s performance in this setting.